Comparative study with extract of Daucus carota seeds and standard market product for wound healing potency (Journal of Advances and Scholarly Researches in Allied Education, 2025)
The present study explores the comparative wound healing potential of Daucus carota (wild carrot) seed extract and a standard commercially available topical formulation, with the aim of validating the traditional use of this medicinal plant in modern dermatological applications. Daucus carota seeds, rich in essential oils, flavonoids, and phenolic compounds, were subjected to ethanolic extraction and formulated into a herbal lotion. The prepared formulation was evaluated alongside a marketed wound healing product using in-vivo excision and incision wound models in Wistar rats. Key wound healing parameters such as percentage of wound contraction, period of epithelialization, tensile strength, and histopathological tissue regeneration were assessed over a defined period. The experimental outcomes revealed that the Daucus carota-based formulation significantly enhanced the rate of wound contraction and epithelialization in comparison to the standard product, with observable improvements in tissue regeneration and tensile strength of the skin. Histological analysis of wound tissues further confirmed the presence of dense collagen fibers, fibroblast proliferation, and reduced inflammatory cell infiltration in the group treated with the herbal formulation. The superior performance of the Daucus carota extract may be attributed to its antimicrobial, antioxidant, and anti-inflammatory properties, which collectively contribute to accelerated wound healing. This research highlights the therapeutic potential of Daucus carota seeds and supports their integration into alternative wound care strategies, offering a cost-effective and natural option with comparable or even superior efficacy to conventional products.